RESPON GURU SEKOLAH DASAR TERHADAP PENGGUNAAN BUKU GURU DALAM IMPLEMENTASI KURIKULUM 2013 - Susilana, Rudi; Alinawati, Muthia (Universitas Pendidikan Indonesia, 2014)
To see the effectiveness of the use of the book, this study examines how the response of teachers, especially primary school teachers to use in the implementation of the Curriculum Master Books, 2013, particularly with respect to one of the main teacher's main task, which is preparing Learning Implementation Plan (RPP). The subjects were elementary school teachers who participated in the Training Curriculum 2013 2014 originating from various districts / cities in West Java Province. Teachers were randomly selected and acquired research subject as many as 150 people. The conclusions of this study are (1) The response of primary school teachers to use in preparing the Master Books Learning Implementation Plan (RPP) on the implementation of Curriculum 2013 in the category generally positive and very positive; (2) There is no difference in the response of teachers to use Teachers guide indeveloping and preparing lesson plans Thematic visits of regional differences assignment (districts); andÂ (3) There are differences in the response of teachers to use of Books Teachers develop and prepare lesson plans Thematic views of component materials / learning experience, component methods / lesson, and components of the assessment, but there are differences in the response of teachers to use of Books Teachers develop and prepare lesKeywords: Implementation of Curriculum 2013, Master Books, Response Teacher.